FORKLÆDTE PENGE: En diskussion af brugerbetaling i en gratis nicaraguansk folkeskole - Jørgensen, Clara Rübner (Tidsskriftet Antropologi, 2018)
On the basis of data collected during fieldwork in the city of León, Nicaragua, this article discusses the paradox of many Nicaraguan parents describing their children’s school as being free of charge despite the fact that they are frequently asked to pay for it. The article shows that, in spite of the constitutional definition of education as free and equal for all Nicaraguans, parents are often asked for economic contributions. By analysing the values surrounding the school I suggest that values of responsibility and solidarity influence the way that parents conceptualize their school expenditures and, in relation to this, confirm the status of the school as free. Furthermore, the article describes how Nicaraguan parents often compare the school to their home and describe the relation between teacher and students by using family terms. Inspired by the theory of the American sociologist James Carrier, I argue that this comparison, in addition to the values of responsibility and solidarity, further influences the way Nicaraguan parents and children experience their economic contributions. Finally, I argue that even though the users of the school describe it as free of charge, it remains necessary to recognize its economic aspects, since a lack of recognition can turn out to have important individual and social consequences for the people involved, especially, for the most economically marginalized families.